ACCELERATING THE USE OF EDUCATIONAL TECHNOLOGY: A PRACTICAL APPROACH TO ICT SUPPORT AT SD INPRES 3 TALISE - Patmasari, Andi; Ismail, Muhammad; Saadillah, Andi; Ahmar, Dewi Satria; Azzajjad, Muhammad Fath (LPPM Univ. Ibn Khaldun Bogor, 2024)
SD Inpres 3 Talise, located in the Palu Disaster Alert Area, was the target of the community service activity